THE ROLE OF PHENOLICS IN AGARWOOD FORMATION OF Aquilaria crassna Pierre ex Lecomte AND Aquilaria microcarpa Baill TREES - Novriyanti, Eka; Santosa, Erdy (Secretariat of Forestry Research and Development Agency, 2011)
Phenolic is well known as a secondary metabolite that plays an important role in plant defense system. Information about the fungi-impeded role of secondary metabolite is important in achieving success of artificial agarwood production, in that fungi induction imparted to the selected potential trees will be more effective and efficient. This research was aimed to investigate the correlation of agarwood tree phenolics in relation with the susceptibility of corresponding trees to Fusarium solani attack in the formation of agarwood and observing total phenolics content of Aquilaria crassna and Aquilaria microcarpa trees prior to inoculation. Twenty trees of A. microcarpa at Carita, a Forest Area for Special Function (FASF) and ten of A. crassna at Dramaga Research Forest were inoculated with isolate of F. solani in spiral pattern around their stem from ground level to about 1.5 m in height. Prior to inoculation, wood strips were taken off from the stem for total phenolics content. The result revealed that total phenolics content and infection area tended to have a negative correlation. Since the quantity of agarwood is highly related with the infection area, then trees with lower phenolics content should be selected for the more effective and efficient artificial agarwood production.